PELATIHAN ANGER MANAGEMENT UNTUK MENGEMBANGKAN REGULASI EMOSI SISWA DI SMK MUHAMMADIYAH SE-KECAMATAN LENDAH, KULONPROGO, YOGYAKARTA - Wahyu Nanda Eka Saputra; Agus Supriyanto; Irvan Budhi Handaka (Bagimu Negeri, 2017)
Aggressive behavior becomes a classic problem that still occurs today. One technique of changing behavior, especially aggression in students is to apply anger management training. Activities that train students to manage anger is composed of eight meetings by using counseling, training, and FGD. Anger management can train students in regulating emotions so that students are able to learn to minimize aggressive behavior. This activity can provide advice for counselors, counselors should train students in carrying out the anger management to enable them to regulate their emotions and the emotions of students not terluap in the form of aggressive behavior when they deal with certain situations.